Cationic antibacterial flame-retardant fiber and preparation method thereof
Through the two-component composite spinning process, cationic antibacterial flame retardant fibers with a leather core structure were prepared, which solved the problem of the weakening of the antibacterial properties of existing antibacterial polyester materials over time, and achieved the long-term antibacterial and flame retardant properties of the fiber, taking into account the strength and application breadth of the fiber.
Patent Information
- Application Number
- CN202411837917.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
AI Technical Summary
During the use of existing antibacterial polyester materials, the antibacterial agent is gradually released, resulting in the gradual weakening of the antibacterial performance over time, and the failure to achieve a lasting antibacterial effect. In addition, the addition of flame retardant usually affects the strength of the fiber, making it difficult to take into account both antibacterial, flame retardant and fiber properties.
Two-component composite spinning process is used to prepare cationic antibacterial flame retardant fibers with a leather core structure. By preparing high-temperature polymerizable cationic antibacterial agents, and esterified and polycondensed with raw materials such as refined terephthalic acid and ethylene glycol, antibacterial polyester and flame retardant polyester are formed, which serve as the leather and core layers of the fiber respectively.
The long-term antibacterial properties of the fiber are achieved. The addition of antibacterial agents does not affect the material properties. The fibers have both antibacterial and flame retardant properties, have good strength, and are suitable for a wide range of applications.
Smart Images

Figure BDA0005187217440000121 
Figure BDA0005187217440000122
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antibacterial materials, and in particular to a cationic antibacterial flame-retardant fiber and a preparation method thereof. Background Art
[0002] Antibacterial materials for textiles are mainly coated, dipped, sprayed and other methods to make fabrics have antibacterial effects. The antibacterial treatment methods for conventional chemical fibers and regenerated fibers are mainly the preparation of antibacterial slices and the addition of antibacterial agents during the spinning process. The currently mature antibacterial polyester materials achieve the antibacterial purpose through the migration of antibacterial agents. The antibacterial polyester prepared by this method gradually releases the antibacterial agent over time, and the antibacterial performance gradually weakens, and it is impossible to achieve a lasting antibacterial effect. Organic antibacterial agents have the advantages of high efficiency, broad-spectrum antibacterial, and structural design, but organic antibacterial agents have poor temperature resistance and are difficult to add through polymerization processes. The post-finishing process, that is, the antibacterial agent is grafted to the surface of the polyester fiber through a chemical reaction. Usually, because the polyester fiber has no reactive functional groups, it is necessary to introduce reactive functional groups on the surface of the polyester fiber through high-energy radiation and other methods, which also leads to the deterioration of the mechanical properties of the fiber. The addition of flame retardants usually affects the strength of the fiber. It is still a challenge to design and prepare a fiber that has both antibacterial and flame retardant functions and takes into account the fiber substrate performance to meet weaving and application requirements.
[0003] A high temperature resistant polymerizable cationic antibacterial agent was prepared, and antibacterial polyester was obtained through an in-situ polymerization process. Antibacterial polyester and flame retardant polyester were used to prepare polyester fibers with both antibacterial and flame retardant properties through a two-component spinning process. Summary of the invention
[0004] The purpose of the present invention is to provide a fiber which is easy to operate, has a simple preparation process, and has both antibacterial and flame retardant properties.
[0005] In order to achieve the above object, the technical solution of the present invention is:
[0006] The antibacterial flame retardant fiber is composed of two-component composite spinning, and the fiber cross section is a skin-core structure. The preparation method includes the following steps:
[0007] Step 1, preparing a high temperature resistant polymerizable cationic antibacterial agent; firstly preparing a carboxyl-containing cationic antibacterial agent, and then performing cation exchange with 4-sulfobenzoic acid monopotassium salt (CAS: 5399-63-3) in water, and the resulting precipitate is the high temperature resistant polymerizable antibacterial agent;
[0008] Step 2, preparation of skin material (cationic antibacterial polyester): using purified terephthalic acid, high temperature resistant polymerizable cationic antibacterial agent and ethylene glycol as raw materials, adding auxiliary trimethyl phosphate, antioxidant, catalyst ethylene glycol antimony. The acid / alcohol molar ratio is 1:1.25, the above substances are prepared into a uniform slurry, added to the esterification reactor, the reactor pressure is controlled at 0.2-0.4MPa, and the reaction temperature is controlled at 240-260℃. The end point of the esterification reaction is determined based on the esterification water amount reaching the theoretical calculation, and the calculation formula of the esterification water amount is: esterification water amount (kg) = total molar number of acid components in the reaction system × 36 × 98%.
[0009] After the esterification is completed, the polycondensation stage begins. The pressure is steadily pumped from normal pressure to an absolute pressure below 1 KPa, the reaction temperature is controlled at 260-270°C, and the time is controlled at 40-60 min. The vacuum is continued to be pumped to an absolute pressure below 100 Pa, the reaction temperature is controlled at 270-290°C, and the time is controlled at 60-120 min. The end point of the polycondensation reaction is determined based on when the polymer viscosity reaches the target viscosity value. After the reaction is completed, nitrogen is filled in, and the pressurized material is discharged through underwater granulation to obtain cationic antibacterial polyester.
[0010] Step 3, prepare the core material (flame retardant polyester): use purified terephthalic acid and ethylene glycol as raw materials, add auxiliary trimethyl phosphate, antioxidant and catalyst ethylene glycol antimony. The acid / alcohol molar ratio is 1:1.25, and the above substances are mixed into a uniform slurry and added into the esterification reactor. The pressure of the reactor is controlled at 0.2-0.4MPa, and the reaction temperature is controlled at 240-260℃. The end point of the esterification reaction is determined based on the calculation of the amount of esterification water. The calculation formula of the amount of esterification water is: Esterification water (kg) = total molar number of acid components in the reaction system × 36 × 98%.
[0011] After the esterification is completed, the polycondensation stage is entered, and the polycondensation stage is divided into a normal pressure stage, a low vacuum stage and a high vacuum stage; in the normal pressure stage, an ethylene glycol solution (50wt%) of 2-carboxyethylphenyl phosphite is added, the temperature is controlled at 250-260°C, and the time is 30min; in the low vacuum stage, the pressure is steadily pumped from normal pressure to an absolute pressure below 1KPa, the reaction temperature is controlled at 260-270°C, and the time is controlled at 40-60min; the vacuum is continuously pumped to an absolute pressure below 100Pa, the reaction temperature is controlled at 270-290°C, and the time is controlled at 60-120min. The end point of the polycondensation reaction is judged based on when the polymer viscosity reaches the target viscosity value. After the reaction is completed, nitrogen is filled, and the material is pressurized and discharged to obtain the cationic antibacterial polyester through underwater granulation.
[0012] Step 4, spinning: the cationic antibacterial polyester and flame retardant polyester pellets are dried to a moisture content of less than 30 ppm, added to their respective single screw extruders, and after melt extrusion, enter the composite spinning assembly to form fibers with a skin-core structure. The fibers are processed into long fibers or short fibers through steps such as cooling, oiling, drawing, and shaping.
[0013] Preferably, in step 1, p-chloromethylbenzoic acid may also be p-bromomethylbenzoic acid, chloroacetic acid, chloropropionic acid, bromoacetic acid, etc.
[0014] Preferably, in step 1, the organic solvent comprises a mixture of one or more of ethyl acetate, tetrahydrofuran, acetone, petroleum ether and acetonitrile.
[0015] Preferably, in step 1, triphenylphosphine may also be tricyclohexylphosphine, N-alkylimidazole, N,N-dimethylalkyl tertiary amine, alkylpiperazine, alkylmorpholine, alkylpiperidine, etc.
[0016] Preferably, in step 1, the molar ratio of p-chloromethylbenzoic acid to triphenylphosphine is 1:1-2.
[0017] Preferably, in step 1, the reaction temperature is 50-140°C.
[0018] Preferably, in step 1, the reaction time is 4-48 hours.
[0019] Preferably, in step 1, the molar ratio of the carboxyl-containing cationic antibacterial agent to 4-sulfobenzoic acid monopotassium salt is 1:1.1-1.5.
[0020] Preferably, in step 2, the molar ratio of the high temperature resistant polymerizable cationic antibacterial agent to purified terephthalic acid is 3%:97%-10%:90%.
[0021] Preferably, in step 2 and step 3, the purified terephthalic acid may be a composite of one or more of 2,5-furandicarboxylic acid, isophthalic acid, phthalic acid, succinic acid, 2,6-naphthalene dicarboxylic acid, pimelic acid, suberic acid, sodium 5-sulfonate of isophthalic acid, and the like.
[0022] Preferably, in step 2 and step 3, the ethylene glycol may be a combination of one or more of propylene glycol, butylene glycol, hexylene glycol, pentylene glycol, polyethylene glycol, 1,4-cyclohexanedimethanol, catechol, hydroquinone, 1,3-adamantanediol, etc.
[0023] Preferably, in step 2 and step 3, the content of trimethyl phosphate is 0.03-0.05%.
[0024] Preferably, in step 2 and step 3, the antimony glycolate may be a composite of one or more of trifluoromethanesulfonic acid, stannous oxide, butyl titanate, sodium acetate, etc., and the amount of the catalyst used is 0.2%-2%.
[0025] Preferably, in step 2 and step 3, the antioxidant is a combination of one or more of antioxidant 1010, antioxidant 168, etc., and the amount of the antioxidant is 1%-3%.
[0026] Preferably, in step 2 and step 3, the intrinsic viscosity of the prepared polyester pellets is 0.65-0.75 dl / g.
[0027] Preferably, in step 3, the phosphorus content in the flame retardant polyester pellets is 1%-3%.
[0028] Preferably, in step 4, the fiber prepared is a skin-core structure, with the core layer accounting for 70-90% and the skin layer accounting for 10-30%.
[0029] Preferably, in step 4, the fiber strength of the prepared fiber is ≥2.8 cN / dtex, the limiting oxygen index is ≥29%, and the antibacterial rate meets the AAA standard.
[0030] The beneficial effects of the present invention are:
[0031] 1. The thermal decomposition temperature of the high temperature resistant polymerizable cationic antibacterial agent prepared by the present invention is higher than 300°C, and the preparation method is simple to operate, has high yield, and can be prepared on a large scale.
[0032] 2. Compared with polyester prepared by traditional blending, the polyester fiber prepared by the present invention has long-lasting antibacterial effect, and the addition of antibacterial agent will not affect the performance of the material, and the antibacterial agent has no dissolution effect, and has a high safety factor.
[0033] 3. The fiber of the skin-core structure of the present invention has both antibacterial and flame retardant properties, good strength and a wide range of applications. DETAILED DESCRIPTION
[0034] In order to further explain the technical solution of the present invention, the present invention is described in detail below through specific embodiments. The embodiments are only used to explain the content of the present invention and are not intended to limit the protection scope of the present invention.
[0035] Example 1
[0036] (1) Preparation of high temperature resistant polymerizable cationic antimicrobial agent: 1.70 kg of p-chloromethylbenzoic acid was dissolved in 20 kg of ethyl acetate, and 2.8 kg of N, N-dimethylhexadecylamine was added under stirring, the temperature was raised to 90°C, and refluxed and stirred for 10 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was washed with ethyl acetate for several times, and dried to obtain N-(4-carboxybenzyl)-N, N-dimethyldodecylammonium chloride. 4.4 kg of N-(4-carboxybenzyl)-N, N-dimethylhexadecylammonium chloride was dissolved in 25 kg of deionized water, and 3.1 kg of 4-sulfobenzoic acid monopotassium salt was added under stirring. The mixture was stirred for 30 minutes, and a large amount of white precipitate was produced. The mixture was filtered, and the filter cake was washed with water for several times, and dried to obtain a high temperature resistant polymerizable cationic antimicrobial agent.
[0037] (2) Preparation of antibacterial polyester pellets: 3.8 kg of purified terephthalic acid, 0.7 kg of the above-mentioned high temperature resistant cationic antibacterial agent and 1.9 kg of ethylene glycol, 0.76 g of trimethyl phosphate, 20 g of antioxidant 1010 and 2.53 g of ethylene glycol antimony were added to form a uniform slurry, which was added to the esterification reactor through a pump, and the air in the reaction device was replaced with nitrogen. The reaction temperature was controlled to be 250°C and the reaction pressure was 0.03 MPa. The reaction was fully stopped when no water was generated, so that the diol and the dibasic acid underwent esterification reaction to generate low molecular weight polymers. In the ester exchange stage, the vacuum degree in the reaction device was reduced by program control from normal pressure to an absolute pressure of less than 1 KPa, the time was controlled to be 40 min, the reaction temperature was controlled to be 260°C, and the vacuum was continued to be evacuated to an absolute pressure of less than 100 Pa, the reaction temperature was 275°C, the reaction time was 1 h, the material was discharged under pressure, and underwater granulation was performed to obtain antibacterial polyester pellets with an intrinsic viscosity of 0.64 dL / g.
[0038] (3) Preparation of flame-retardant polyester pellets: 4.0 kg of purified terephthalic acid and 1.9 kg of ethylene glycol were added with 0.76 g of trimethyl phosphate, 20 g of antioxidant 1010 and 2.53 g of ethylene glycol antimony to form a uniform slurry, which was added to an esterification reactor via a pump, and the air in the reaction device was replaced with nitrogen. The reaction temperature was controlled to be 250° C. and the reaction pressure was 0.03 MPa. The reaction was fully stopped when no water was generated, so that the diol and the dibasic acid were esterified to form a low molecular weight polymer. After the esterification reaction was completed, 120 g of ethylene glycol solution (50 wt%) of 2-carboxyethylphenylphosphite was added, and the reaction time was maintained at 255° C. The equilibrium time was 30 min. After the equilibrium time is over, the vacuum degree in the reaction device is reduced by program control from normal pressure to an absolute pressure below 1 KPa, the time is controlled at 40 min, the reaction temperature is controlled at 260°C, and the vacuum is continued to be pumped to an absolute pressure below 100 Pa, the reaction temperature is 275°C, the reaction time is 60 min, the material is pressurized and granulated underwater to obtain flame-retardant polyester pellets with a characteristic viscosity of 0.65 dL / g.
[0039] (4) Spinning experiment: 0.2 kg of antibacterial polyester as the skin layer and 0.8 kg of flame retardant polyester as the core layer were fully dried to a moisture content of less than 30 ppm, respectively added into respective single-screw extruders, and melt-spun to form fibers with a skin-core structure.
[0040] Example 2
[0041] (1) Preparation of high temperature resistant polymerizable cationic antimicrobial agent: 1.70 kg of p-chloromethylbenzoic acid was dissolved in 30 kg of ethyl acetate, and 3.5 kg of N-hexadecyl imidazole was added under stirring, the temperature was raised to 85°C, and refluxed and stirred for 8 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was washed with ethyl acetate for several times, and dried to obtain N-(4-carboxybenzyl)-N-hexadecyl imidazole ammonium chloride. 4.6 kg of N-(4-carboxybenzyl)-N-hexadecyl imidazole ammonium chloride was dissolved in 30 kg of deionized water, and 3.1 kg of 4-sulfobenzoic acid monopotassium salt was added under stirring, and stirring was continued for 30 minutes. A large amount of white precipitate was produced, filtered, and the filter cake was washed with water for several times, and dried to obtain a high temperature resistant polymerizable cationic antimicrobial agent.
[0042] (2) Preparation of antibacterial polyester pellets: 3.8 kg of purified terephthalic acid, 0.75 kg of the above-mentioned high temperature resistant cationic antibacterial agent and 1.9 kg of ethylene glycol, 0.76 g of trimethyl phosphate, 20 g of antioxidant 1010 and 2.53 g of ethylene glycol antimony were added to form a uniform slurry, which was added to the esterification reactor through a pump, and the air in the reaction device was replaced with nitrogen. The reaction temperature was controlled to be 250°C and the reaction pressure was 0.03 MPa. The reaction was fully stopped when no water was generated, so that the diol and the dibasic acid underwent esterification reaction to generate low molecular weight polymers. In the ester exchange stage, the vacuum degree in the reaction device was reduced by program control from normal pressure to an absolute pressure of less than 1 KPa, the time was controlled to be 40 min, the reaction temperature was controlled to be 260°C, and the vacuum was continued to be evacuated to an absolute pressure of less than 100 Pa, the reaction temperature was 275°C, the reaction time was 65 min, the material was discharged under pressure, and underwater granulation was performed to obtain antibacterial polyester pellets with an intrinsic viscosity of 0.67 dL / g.
[0043] (3) Preparation of flame-retardant polyester pellets: 4.0 kg of purified terephthalic acid and 1.9 kg of ethylene glycol were added with 0.76 g of trimethyl phosphate, 20 g of antioxidant 1010 and 2.53 g of ethylene glycol antimony to form a uniform slurry, which was added to an esterification reactor via a pump, and the air in the reaction device was replaced with nitrogen. The reaction temperature was controlled to be 250° C. and the reaction pressure was 0.03 MPa. The reaction was fully stopped when no water was generated, so that the diol and the dibasic acid were esterified to form a low molecular weight polymer. After the esterification reaction was completed, 160 g of 2-carboxyethylphenylphosphite in ethylene glycol solution (50 wt%) was added, and the reaction time was maintained at 255° C. and the equilibrium time was 30 min. After the equilibrium time is over, the vacuum degree in the reaction device is reduced by program control from normal pressure to an absolute pressure below 1 KPa, the time is controlled at 40 min, the reaction temperature is controlled at 260°C, and the vacuum is continued to be pumped to an absolute pressure below 100 Pa, the reaction temperature is 275°C, the reaction time is 65 min, the material is discharged under pressure, and granulation is performed underwater to obtain flame-retardant polyester pellets with a characteristic viscosity of 0.66 dL / g.
[0044] (4) Spinning experiment: 0.3 kg of antibacterial polyester as the skin layer and 0.7 kg of flame retardant polyester as the core layer were fully dried to a moisture content of less than 30 ppm, respectively added to their respective single-screw extruders, and melt-spun to form fibers with a skin-core structure.
[0045] Example 3
[0046] (1) Preparation of high temperature resistant polymerizable cationic antimicrobial agent: 1.70 kg of p-chloromethylbenzoic acid was dissolved in 30 kg of ethyl acetate, and 2.6 kg of triphenylphosphine was added under stirring, the temperature was raised to 88°C, and refluxed and stirred for 9 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was washed with ethyl acetate for several times, and dried to obtain quaternary phosphonium salt. 4.3 kg of quaternary phosphonium salt was dissolved in 28 kg of deionized water, and 3.1 kg of 4-sulfobenzoic acid monopotassium salt was added under stirring, and stirring was continued for 30 minutes. A large amount of white precipitate was produced, filtered, and the filter cake was washed with water for several times, and dried to obtain high temperature resistant polymerizable cationic antimicrobial agent.
[0047] (2) Preparation of antibacterial polyester pellets: 3.868 kg of purified terephthalic acid, 0.431 kg of the above-mentioned high-temperature resistant cationic antibacterial agent and 1.95 kg of ethylene glycol were added with 0.76 g of trimethyl phosphate, 22 g of antioxidant 1010 and 2.55 g of ethylene glycol antimony to form a uniform slurry, which was added into an esterification reactor via a pump. The air in the reaction apparatus was replaced with nitrogen. The reaction temperature was controlled to be 250°C and the reaction pressure was controlled to be 0.03 MPa. The reaction was stopped when no water was generated, so that the diol and the dibasic acid underwent an esterification reaction to generate a low molecular weight polymer. During the ester exchange stage, the vacuum degree in the reaction device was reduced through program control from normal pressure to an absolute pressure below 1 KPa, the time was controlled at 40 min, the reaction temperature was controlled at 260°C, and the vacuum was continued to be pumped to an absolute pressure below 100 Pa, the reaction temperature was 275°C, the reaction time was 60 min, the material was discharged under pressure, and underwater granulation was performed to obtain antibacterial polyester pellets with a characteristic viscosity of 0.66 dL / g.
[0048] (3) Preparation of flame-retardant polyester pellets: 4.0 kg of purified terephthalic acid and 1.9 kg of ethylene glycol were added with 0.76 g of trimethyl phosphate, 22 g of antioxidant 1010 and 2.55 g of ethylene glycol antimony to form a uniform slurry, which was added to an esterification reactor via a pump, and the air in the reaction device was replaced with nitrogen. The reaction temperature was controlled to be 250° C. and the reaction pressure was 0.03 MPa. The reaction was fully stopped when no water was generated, so that the diol and the dibasic acid were esterified to form a low molecular weight polymer. After the esterification reaction was completed, 120 g of ethylene glycol solution (50 wt%) of 2-carboxyethylphenylphosphite was added, and the reaction time was maintained at 255° C. The equilibrium time was 30 min. After the equilibrium time is over, the vacuum degree in the reaction device is reduced by program control from normal pressure to an absolute pressure below 1 KPa, the time is controlled at 40 min, the reaction temperature is controlled at 260°C, and the vacuum is continued to be pumped to an absolute pressure below 100 Pa, the reaction temperature is 275°C, the reaction time is 60 min, the material is discharged under pressure, and granulation is performed underwater to obtain flame-retardant polyester pellets with a characteristic viscosity of 0.66 dL / g.
[0049] (4) Spinning experiment: 0.2 kg of antibacterial polyester as the skin layer and 0.8 kg of flame retardant polyester as the core layer were fully dried to a moisture content of less than 30 ppm, respectively added into respective single-screw extruders, and melt-spun to form fibers with a skin-core structure.
[0050] Comparative Example 1
[0051] (1) Preparation of antibacterial polyester: 4.0 kg of purified terephthalic acid and 1.9 kg of ethylene glycol were added with 0.76 g of trimethyl phosphate, 20 g of antioxidant 1010 and 2.53 g of ethylene glycol antimony to form a uniform slurry, which was added to the esterification reactor through a pump, and the air in the reactor was replaced with nitrogen. The reaction temperature was controlled to be 250°C and the reaction pressure was 0.03 MPa. The reaction was fully stopped when no water was generated, so that the diol and the dibasic acid underwent esterification to generate low molecular weight polymers. In the ester exchange stage, the vacuum degree in the reactor was reduced by program control from normal pressure to an absolute pressure of less than 1 KPa, the time was controlled to be 40 min, the reaction temperature was controlled to be 260°C, and the vacuum was continued to be evacuated to an absolute pressure of less than 100 Pa, the reaction temperature was 275°C, the reaction time was 65 min, the material was discharged under pressure, and underwater granulation was performed to obtain ordinary polyester pellets with an intrinsic viscosity of 0.64 dL / g.
[0052] (2) Spinning experiment: The polyester prepared above was fully dried to a moisture content of less than 30 ppm, added to a spinning machine, and melt-spinned to obtain polyester fibers.
[0053] Comparative Example 2
[0054] (1) Preparation of high temperature resistant polymerizable cationic antimicrobial agent: 1.70 kg of p-chloromethylbenzoic acid was dissolved in 30 kg of ethyl acetate, and 3.5 kg of N-hexadecyl imidazole was added under stirring, the temperature was raised to 85°C, and refluxed and stirred for 8 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was washed with ethyl acetate for several times, and dried to obtain N-(4-carboxybenzyl)-N-hexadecyl imidazole ammonium chloride. 4.6 kg of N-(4-carboxybenzyl)-N-hexadecyl imidazole ammonium chloride was dissolved in 30 kg of deionized water, and 3.1 kg of 4-sulfobenzoic acid monopotassium salt was added under stirring, and stirring was continued for 30 minutes. A large amount of white precipitate was produced, filtered, and the filter cake was washed with water for several times, and dried to obtain a high temperature resistant polymerizable cationic antimicrobial agent.
[0055] (2) Preparation of antibacterial polyester pellets: 3.8 kg of purified terephthalic acid, 0.75 kg of the above-mentioned high temperature resistant cationic antibacterial agent and 1.9 kg of ethylene glycol, 0.76 g of trimethyl phosphate, 20 g of antioxidant 1010 and 2.53 g of ethylene glycol antimony were added to form a uniform slurry, which was added to the esterification reactor through a pump, and the air in the reaction device was replaced with nitrogen. The reaction temperature was controlled to be 250°C and the reaction pressure was 0.03 MPa. The reaction was fully stopped when no water was generated, so that the diol and the dibasic acid underwent esterification reaction to generate low molecular weight polymers. In the ester exchange stage, the vacuum degree in the reaction device was reduced by program control from normal pressure to an absolute pressure of less than 1 KPa, the time was controlled to be 40 min, the reaction temperature was controlled to be 260°C, and the vacuum was continued to be evacuated to an absolute pressure of less than 100 Pa, the reaction temperature was 275°C, the reaction time was 65 min, the material was discharged under pressure, and underwater granulation was performed to obtain antibacterial polyester pellets, whose intrinsic viscosity was 0.66 dL / g.
[0056] (3) Spinning experiment: 0.2 kg of antibacterial polyester as the skin layer and 0.8 kg of the ordinary polyester prepared in Comparative Example 1 as the core layer were fully dried to a moisture content of less than 30 ppm and added to respective single-screw extruders to form fibers with a skin-core structure after melt spinning.
[0057] Comparative Example 3
[0058] (1) Preparation of flame-retardant polyester pellets: 4.0 kg of purified terephthalic acid and 1.9 kg of ethylene glycol were added with 0.76 g of trimethyl phosphate, 20 g of antioxidant 1010 and 2.53 g of ethylene glycol antimony to form a uniform slurry, which was added to an esterification reactor via a pump, and the air in the reaction device was replaced with nitrogen. The reaction temperature was controlled to be 250° C. and the reaction pressure was 0.03 MPa. The reaction was fully stopped when no water was generated, so that the diol and the dibasic acid were esterified to form a low molecular weight polymer. After the esterification reaction was completed, 60 g of ethylene glycol solution (50 wt%) of 2-carboxyethylphenylphosphite was added, and the reaction time was maintained at 255° C. and the equilibrium time was 30 min. After the equilibrium time is over, the vacuum degree in the reaction device is reduced by program control from normal pressure to an absolute pressure below 1 KPa, the time is controlled at 40 min, the reaction temperature is controlled at 260°C, and the vacuum is continued to be pumped to an absolute pressure below 100 Pa, the reaction temperature is 275°C, the reaction time is 65 min, the material is discharged under pressure, and underwater granulation is performed to obtain flame-retardant polyester pellets with a characteristic viscosity of 0.68 dL / g.
[0059] (2) Spinning experiment: The flame retardant polyester pellets were fully dried to a moisture content of less than 30 ppm, added to a single screw extruder, and melt-spinned to obtain flame retardant fibers.
[0060] Main indicator test methods:
[0061] (1) Intrinsic viscosity of polyester pellets: GB / T 14190-2008;
[0062] (2) Fiber strength: GB / T 8960-2015;
[0063] (3) Antibacterial properties: FZ / T 73023-2006;
[0064] (4) Limiting oxygen index: GB / T 5454-1997.
[0065] Main test results:
[0066] Table 1 Fiber strength of cationic antibacterial flame retardant fibers
[0067] Group Single fiber strength (cN / tex) Example 1 3.5 Example 2 3.3 Example 3 3.6 Comparative Example 1 3.7 Comparative Example 2 3.6 Comparative Example 3 3.2
[0068] The results of the single fiber strength test show that the addition of antimicrobial agents has little effect on the strength of single fibers; on the contrary, the addition of flame retardants will reduce the strength of the fibers. This may be due to the poor dispersion of flame retardants in polyester, which partially agglomerates and reduces the processing performance of spinning. The prepared high-temperature resistant polymerizable cationic antimicrobial agent contains two carboxyl groups, which participate in the reaction during the polymerization process and are evenly distributed in polyester, so the effect on the strength of the fibers is not obvious.
[0069] Table 2 Antibacterial properties of polyester fibers before and after washing
[0070]
[0071] Table 3 Antibacterial rate index of antibacterial knitwear
[0072]
[0073] The results of Table 2 and Table 3 above show that by introducing the high temperature resistant polymerizable antibacterial agent into the polyester structure by copolymerization, and by two-component spinning, with the antibacterial polyester as the cortex, a fiber with excellent antibacterial properties can be obtained. The antibacterial agent is copolymerized in the molecular chain and has excellent washing resistance. After 50 times of washing, its antibacterial rate is close to that before washing, and the antibacterial grade is AAA. In addition, if the flame retardant function is not required in the use environment, the method of Comparative Example 2 can be used to prepare polyester fibers with antibacterial functions. The antibacterial fiber prepared by this method has the advantages of less antibacterial agent usage and low production cost.
[0074] Table 4 Limiting oxygen index of cationic antibacterial flame retardant fibers
[0075] Group Limiting oxygen index LOI (%) Example 1 33 Example 2 29 Example 3 32 Comparative Example 1 23 Comparative Example 2 26 Comparative Example 3 33
[0076] The results in Table 4 show that the introduction of flame retardants can improve the limiting oxygen index of polyester fibers. And through the results of Comparative Examples 1 and 2, it can be found that the introduction of the prepared high temperature resistant polymerizable cationic antibacterial agent has a positive effect on improving the flame retardant properties of the fiber to a certain extent. For fibers that do not require antibacterial function, the preparation process of Comparative Example 3 can be used, or a composite spinning method can be used to give the flame retardant fiber a new function.
[0077] The above results show that the cationic antibacterial flame retardant fiber prepared by this method not only has good mechanical properties, but also has excellent flame retardant and antibacterial properties, meeting the AAA grade standard. The introduction of cationic antibacterial agents also has a certain promoting effect on flame retardancy.
[0078] The above embodiments do not limit the method of the present invention, and any appropriate changes or modifications made by ordinary technicians in the relevant technical field should be deemed to be within the patent scope of the present invention.
Claims
1. A cationic antibacterial flame-retardant fiber and a preparation method thereof, characterized in that: The cationic antibacterial flame-retardant fiber is composed of two-component composite spinning, and the fiber cross section is a skin-core structure. The preparation method comprises the following steps: (1) Preparing a high temperature resistant polymerizable cationic antibacterial agent; first preparing a carboxyl-containing cationic quaternary ammonium salt, and then performing cation exchange with 4-sulfobenzoic acid monopotassium salt (CAS: 5399-63-3) in water, and the resulting precipitate is the high temperature resistant polymerizable antibacterial agent; (2) Preparation of skin material (cationic antibacterial polyester): using purified terephthalic acid, high temperature resistant polymerizable cationic antibacterial agent and ethylene glycol as raw materials, adding auxiliary agent trimethyl phosphate, antioxidant, and catalyst ethylene glycol antimony. The acid / alcohol molar ratio is 1:1.25, and the above substances are mixed into a uniform slurry and added into the esterification reactor. The pressure of the reactor is controlled at 0.2-0.4Mpa, and the reaction temperature is controlled at 240-260℃. After the esterification is completed, it enters the polycondensation stage, and the pressure is steadily pumped from normal pressure to an absolute pressure below 1Kpa, and the reaction temperature is controlled at 260-270℃, and the time is controlled at 40-60min; continue to vacuumize to an absolute pressure below 100Pa, and the reaction temperature is controlled at 270-290℃, and the time is controlled at 60-120min. After the reaction is completed, the material is pressurized and discharged, and then granulated underwater to obtain cationic antibacterial polyester. (3) Preparation of core layer material (flame retardant polyester): Using purified terephthalic acid and ethylene glycol as raw materials, adding auxiliary agent trimethyl phosphate, antioxidant and catalyst ethylene glycol antimony. The acid / alcohol molar ratio is 1:1.
25. The above substances are mixed into a uniform slurry and added into an esterification reactor. The reactor pressure is controlled at 0.2-0.4Mpa and the reaction temperature is controlled at 240-260℃. After the esterification is completed, the polycondensation stage is entered, and the polycondensation stage is divided into a normal pressure stage, a low vacuum stage and a high vacuum stage; in the normal pressure stage, an ethylene glycol solution (50wt%) of 2-carboxyethylphenyl phosphite is added, the temperature is controlled at 250-260°C, and the reaction time is 30 minutes; in the low vacuum stage, the pressure is steadily pumped from normal pressure to an absolute pressure below 1KPa, the reaction temperature is controlled at 260-270°C, and the reaction time is controlled at 40-60 minutes; the vacuum is continuously pumped to an absolute pressure below 100Pa, the reaction temperature is controlled at 270-290°C, and the reaction time is controlled at 60-120 minutes, and after the reaction is completed, the material is pressurized and discharged, and underwater granulation is performed to obtain flame-retardant polyester. (3) Spinning: The cationic antibacterial polyester and flame retardant polyester pellets are dried to a moisture content of less than 30 ppm, respectively added to their respective single-screw extruders, and after melt extrusion, enter the composite spinning assembly to form fibers with a skin-core structure. The fibers can be processed into long fibers or short fibers through steps such as cooling, oiling, drawing, and shaping.
2. The cationic antibacterial flame retardant fiber and the preparation method thereof according to claim 1, characterized in that: The high temperature resistant polymerizable cationic antibacterial agent is prepared by the following steps: Step 1, dissolving p-chloromethylbenzoic acid in an organic solvent to obtain a p-chloromethylbenzoic acid solution with a mass percentage concentration of 0.5-20%; adding triphenylphosphine to the above solution, increasing the reaction temperature, and continuing the reaction to precipitate a large amount of solid; after the reaction is completed, filtering, washing, drying, etc. to obtain a quaternary phosphonium salt containing a monocarboxyl group; Step 2: dissolving the monocarboxyl-containing quaternary phosphonium salt obtained in step 1 in water to obtain a 20% solution, adding 4-sulfobenzoic acid monopotassium salt under stirring, and a large amount of precipitate is precipitated during the reaction, wherein the molar ratio of the monocarboxyl quaternary phosphonium salt to the 4-sulfobenzoic acid monopotassium salt is 1:1.1-1.
5.
3. In step 1 as described in claim 2, p-chloromethylbenzoic acid may also be p-bromomethylbenzoic acid, chloroacetic acid, chloropropionic acid, bromoacetic acid, etc.; the organic solvent comprises a mixture of one or more of ethyl acetate, tetrahydrofuran, acetone, petroleum ether and acetonitrile; triphenylphosphine may be tricyclohexylphosphine, N-alkylimidazole, N,N-dimethylalkyl tertiary amine, alkylpiperazine, alkylmorpholine, alkylpiperidine, etc.; the molar ratio of p-chloromethylbenzoic acid to triphenylphosphine is 1:1-2; the reaction temperature is 50-140°C; and the reaction time is 4-48h.
4. The cationic antibacterial flame retardant fiber and the preparation method thereof according to claim 1, characterized in that: The molar ratio of the high temperature resistant polymerizable cationic antibacterial agent to purified terephthalic acid is 3%:97%-10%:90%.
5. The cationic antibacterial flame retardant fiber and the preparation method thereof according to claim 1, characterized in that: The phosphorus content in flame retardant polyester pellets is 1%-3%.
6. The cationic antibacterial flame retardant fiber and the preparation method thereof according to claim 1, characterized in that: The antioxidant is antioxidant 1010 and / or antioxidant 168, and the added amount of the antioxidant is 0.5%-1%.
7. The cationic antibacterial flame retardant fiber and the preparation method thereof according to claim 1, characterized in that: The prepared fiber has a skin-core structure, with the core layer accounting for 70-90% and the skin layer accounting for 10-30%.
8. The cationic antibacterial flame retardant fiber and the preparation method thereof according to claim 1, characterized in that: The intrinsic viscosity of the cationic antibacterial polyester and the flame-retardant polyester is 0.65-0.75 dl / g.
9. The cationic antibacterial flame retardant fiber and the preparation method thereof according to claim 7, characterized in that: The fiber strength of the cationic antibacterial flame-retardant fiber is ≥2.8cN / dtex, the limiting oxygen index is ≥29%, and the antibacterial rate meets the AAA standard.
Citation Information
Cited By
Reactive flame-retardant antibacterial auxiliary agent for polyester as well as preparation method and application of reactive flame-retardant antibacterial auxiliary agent
CN121975130A
Polyester reactive flame-retardant antibacterial additive, and preparation method and application thereof
CN121975130B